2018
DOI: 10.1152/ajpheart.00098.2018
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of device-guided slow breathing on sympathetic nerve activity and baroreflex sensitivity in posttraumatic stress disorder

Abstract: Patients with posttraumatic stress disorder (PTSD) have elevated sympathetic nervous system reactivity and impaired sympathetic and cardiovagal baroreflex sensitivity (BRS). Device-guided slow breathing (DGB) has been shown to lower blood pressure (BP) and sympathetic activity in other patient populations. We hypothesized that DGB acutely lowers BP, heart rate (HR), and improves BRS in PTSD. In 23 prehypertensive veterans with PTSD, we measured continuous BP, ECG, and muscle sympathetic nerve activity (MSNA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…In the healthy state, MSNA represents global sympathetic outflow to the skeletal muscle linked to BP regulation with strong feedback from the arterial baroreceptors (Wallin, ) and respiratory modulation (Habler, Janig, & Michaelis, ). The reduction in MSNA observed during slow breathing at either RF or RF + 1 was similar to that demonstrated in previous studies where slow breathing was of 10–15 min duration (Fonkoue et al, ; Harada et al, ; Hering et al, ; Oneda et al, ). Two prior studies in healthy subjects indicated no effect of slow breathing on MSNA but the duration of the breathing exercise was much shorter being 3 (Limberg et al, ) or 4 min (Raupach et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the healthy state, MSNA represents global sympathetic outflow to the skeletal muscle linked to BP regulation with strong feedback from the arterial baroreceptors (Wallin, ) and respiratory modulation (Habler, Janig, & Michaelis, ). The reduction in MSNA observed during slow breathing at either RF or RF + 1 was similar to that demonstrated in previous studies where slow breathing was of 10–15 min duration (Fonkoue et al, ; Harada et al, ; Hering et al, ; Oneda et al, ). Two prior studies in healthy subjects indicated no effect of slow breathing on MSNA but the duration of the breathing exercise was much shorter being 3 (Limberg et al, ) or 4 min (Raupach et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Tzeng et al () demonstrated that slow breathing in healthy subjects did not affect the arterial baroreflex when measured using the gold standard modified Oxford method and suggested that results indicating improvement in baroreflex function during slow breathing may have occurred as commonly used baroreflex assessment techniques may not be accurate in this setting. The sympathetic baroreflex function was also explored as a possible contributor to the changes in MSNA as Fonkue and colleagues observed that slow breathing improved the sympathetic baroreflex function (Fonkoue et al, ). However, this was not observed in our study as neither RF nor RF + 1 improved the slope of the sympathetic baroreflex function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Fonkoue et al. ) and endothelial remodeling (Savoia et al. ) may have a role in impairing arterial BRS at the level of the nucleus tractus solitarii in the brainstem, or the baroreceptor nerve endings within the vasculature, thereby contributing to the maintenance of SNS overactivation and subsequent development of hypertension (Bristow et al.…”
Section: Introductionmentioning
confidence: 99%